AB1163 My behcet's disease and my menstruation cycle: observation from an irish cohort. (12th June 2018) - Ng, W.L.; Adeeb, F.; Sebastian, A.; Anjum, A.; Brady, M.; Gillespie, M.; Irwin, F.; McCarthy, B.; Devlin, J.; Fraser, A.
Abstract : Background: The menstrual cycle is regulated by the rise and fall of sex hormones in the body. Literature has demonstrated anti-inflammatory properties in both progesterone and oestrogen hormones. 1 There has been recent interest to determine the association between Behçet's Disease (BD), a poorly understood autoinflammatory disorder and menstruation. Objectives: The objective of this study was to evaluate the effect of menstruation in triggering exacerbations of Behçet's disease in a Northern European cohort. Methods: 18 female patients from our rheumatology department satisfying the International Study Group for Behçet's Disease (ISGBD) criteria were recruited. A questionnaire was conducted via telephone to determine whether their exacerbations of BD were correlated to their menstrual cycle. Results: All 18 patients responded to the questionnaire, with the mean age of 38.8 years and mean age of menarche of 13 years. Four (22.22%) patients were in menopausal state. Half (nine) of the patients reported that their BD flare ups were correlated to their menstrual cycle. Exacerbations experienced include oral aphthosis (88.9%), arthralgia (55.6%), genital ulcerations (44.4%), lethargy (44.4%), skin lesions (11.1%) and headaches (11.1%). Six of the seven patients (86%) who were on contraception were on a progesterone containing contraception. Four out of nine (44%) who did not notice any exacerbations during menstruation stated that they were on progesterone containing contraceptives. It is noteworthy that 10 patients (55.56%) had previous pregnancies while three patients experienced an episode of miscarriage and 1 had a stillbirth. Conclusions: Our results demonstrated that the disease activity in BD is related to the menstrual cycle, which is contributed by the female sex hormones. The study supports previous hypothesis that the abrupt decline in progesterone during onset of menstruation is associated to disease flare in BD. 2 Studies comprising larger cohorts should be conducted to further support and strengthen this evidence. References: [1] Szekeres-Bartho J, Barakonyi A, Par G, et al. Progesterone as an immunomodulatory molecule. Int J Immunopharmacol. 2001; 1: 1037–48. [2] Bang D, Chun YS, Haam IB, et al. The influence of pregnancy on Behçet's disease. Yonsei Med J. 1997; 38: 437–43 Disclosure of Interest: None declared